RB1-deficient prostate tumor growth and metastasis are vulnerable to ferroptosis induction via the E2F/ACSL4 axis - Wang, Mu-En; Chen, Jiaqi; Lu, Yi; Bawcom, Alyssa R.; Wu, Jinjin; Ou, Jianhong; Asara, John M.; Armstrong, Andrew J.; Wang, Qianben; Li, Lei; Wang, Yuzhuo; Huang, Jiaoti; et al. (The Journal of clinical investigation, 2023)
Inactivation of the RB1 tumor suppressor gene is common in several types of therapy-resistant cancers, including metastatic castration-resistant prostate cancer, and predicts poor clinical outcomes. Effective therapeutic strategies against RB1-deficient cancers remain elusive. Here, we showed that RB1 loss/E2F activation sensitized cancer cells to ferroptosis, a form of regulated cell death driven by iron-dependent lipid peroxidation, by upregulating expression of ACSL4 and enriching ACSL4-dependent arachidonic acid-containing phospholipids, which are key components of ferroptosis execution. ACSL4 appeared to be a direct E2F target gene and was critical to RB1 loss-induced sensitization to ferroptosis. Importantly, using cell line-derived xenografts and genetically engineered tumor models, we demonstrated that induction of ferroptosis in vivo by JKE-1674, a highly selective and stable GPX4 inhibitor, blocked RB1-deficient prostate tumor growth and metastasis and led to improved survival of the mice. Thus, our findings uncover an RB/E2F/ACSL4 molecular axis that governs ferroptosis and also suggest a promising approach for the treatment of RB1-deficient malignancies.